Real Time Network Security Intrusions and Risk Management: A Survey - et. al., Bashayer O. ALOFFI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the massive use of the Internet by people, institutions and organizations for many reasons, so they need to make sure that all their information is safe and free from tampering with their information, theft, disclosure, and misuse of it in a way that could harm them. In general, no one can be able to find an Internet, organizations, companies, or even users' personal devices that are not threatened by security breaches, intrusions, and any kind of attacks. This paper surveys recent researches related to network security intrusions and risk management. In addition, this work aims to clarify how to detect illegal intrusions. Furthermore, evaluate and control risks and reduce them to acceptable levels. Also discussing strategies for managing them